2015
DOI: 10.1016/j.maturitas.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dance interventions in people with Parkinson disease and older adults

Abstract: It is important for our aging population to remain active, particularly those with chronic diseases, like Parkinson disease (PD), which limit mobility. Recent studies in older adults and people with PD suggest dance interventions provide various motor benefits. The literature for dance in PD is growing, but many knowledge gaps remain, relative to what is known in older adults. The purpose of this review is to: 1) detail results of dance intervention studies in older adults and in PD, 2) describe limitations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
1
39
0
1
Order By: Relevance
“…Further, no studies in PD to date examine the effects of dance on other psychiatric disturbances that are common in PD such as anxiety, anhedonia, apathy, and impulse control disorders. In particular, prevalence rates of anxiety disorders in PD range from 19.8% to 67%, and risk factors include depressive symptoms, disease severity, postural instability, and gait dysfunction [37] which dance may help alleviate [15]. People with PD with psychiatric morbidity tend to have poorer outcomes [37], so it is important to identify interventions to address these concerns in addition to motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, no studies in PD to date examine the effects of dance on other psychiatric disturbances that are common in PD such as anxiety, anhedonia, apathy, and impulse control disorders. In particular, prevalence rates of anxiety disorders in PD range from 19.8% to 67%, and risk factors include depressive symptoms, disease severity, postural instability, and gait dysfunction [37] which dance may help alleviate [15]. People with PD with psychiatric morbidity tend to have poorer outcomes [37], so it is important to identify interventions to address these concerns in addition to motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…dance style, control group, frequency, duration, intensity) as well as outcome measures used makes it challenging to determine whether observed differences between groups (or lack thereof) are due to characteristics of the interventions, general physical activity, or social support/education provided in group settings. However, there is a growing body of evidence supporting improvements in non-motor function with dance, in these populations in addition to the well-documented improvements in motor function [15]. Further well-designed research is required to clarify the benefits of dance in PD and healthy older adults, as well as to determine recommendations for optimal interventions in these populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on arts and health centres on how performing arts can best serve people living with debilitating and chronic illness such as dementia, Parkinson's disease, and mental illness (Adam, Ramli, & Shahar, 2016;Coaten & Newman-Bluestein, 2013;Guzman, Freeston, Rochester, Hughes, & James, 2016;Jones, 2016;Karkou & Meekums, 2017;Lannen, Worrall, Alston, Marley, & Allan, 2012;Lapum & Bar, 2016;Särkämö et al, 2016;Sorrell, 2018;Sung & Chang, 2005;Sung, Chang, & Lee, 2010;Verghese et al, 2006). For example, multiple studies have shown that dance therapy can significantly improve gait, movement, balance, and wellbeing in patients with Parkinson's disease (Butt, 2017;Hackney & Earhart, 2010;Hackney & McKee, 2014;Hashimoto, Takabatake, Miyaguchi, Nakanishi, & Naitou, 2015;Karkou & Meekums, 2017;Lewis, Annett, Davenport, Hall, & Lovatt, 2016;McNeely, Duncan, & Earhart, 2015;Rios Romenets, Anang, Fereshtehnejad, Pelletier, & Postuma, 2015;Rocha, Slade, McClelland, & Morris, 2017;Shanahan et al, 2017;Ventura et al, 2016). Music therapy is also a well-established approach to treating a range of issues, such as speech pathologies, poor mental health, and social and behavioural difficulties in children and adults (Edwards, 2011;MacDonald et al, 2012).…”
mentioning
confidence: 99%
“…Aerobic exercise is achieved at the point when the individual's heart rate meets or exceeds 60% of their target heart rate. Research in 2015 showed that dance intervention gave a positive result for curing Parkinson disease and older adults in many fitness components such as flexibility, power, balance, and strength (McNeely et al, 2015). Hence, aerobic dance have high potential to reduce stress (Brauninger, 2012).…”
Section: Introductionmentioning
confidence: 99%